Assess of Impact of Good Training of Health Care Workers on Health Service Improvement - Abdulaziz Hawi Hassan Hakami,; Fatimah Arar Haddur,; Hajer Ahdal Khardali,; Thahbah Ali Mohammed Jarab,; Amal Eissa Bajahnon,; Wed Ahmad Ali Bakren,; Mutaen Muosa Ali Tumaih,; Afaf Shuaib Mohsen Zaylaee,; Majed Abdullah Abduaziz Alshammari,; Halima Ahmed Tala Asiri, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:The effectiveness of healthcare workers is essential in ensuring top-notch healthcare services are provided. Training programs are essential for enhancing the skills, knowledge, and overall performance of healthcare workers. The importance of top-notch training has become increasingly clear in healthcare environments, where technological progress and evolving healthcare requirements demand ongoing skill enhancement. This study delves into the influence of training programs on the performance of healthcare workers, particularly emphasizing a government hospital linked to the Ministry of Health. Methods: A cross-sectional survey research design was employed to investigate the impact of training on the performance of healthcare workers. Data was collected through a questionnaire distributed to 51 healthcare workers employed at the hospital for over one year. The questionnaire included details about demographics, past training experiences, and how training programs were seen to affect their performance. The data was analyzed with the Statistical Package for Social Sciences (SPSS), and descriptive statistics were applied to showcase the results. Results: The study found that the majority of respondents (84%) were female, with 60% of respondents aged 26 to 35 years. Most participants held a bachelor’s degree (64.7%). A significant portion (72.5%) of respondents had undergone training, and 59.5% of them reported that the training aimed at improving performance. A majority of respondents (73%) believed the training methods positively impacted their skills, while 35.1% were satisfied with the training quality. Most participants (59.5%) found the training relevant to their work, and 58.6% indicated a need for further training to improve performance. However, challenges such as inconvenient timing and irregular training schedules were reported by some respondents. Conclusion: The study concluded that training programs significantly impact the performance of HCWs by enhancing their knowledge and skills. While training is a vital tool for improving healthcare delivery, it is not the only factor contributing to performance. Future research should examine the design and needs assessment of training programs, as well as managerial factors that could influence the effectiveness of training and its impact on HCWs' performance.